Seismic Response of the Central Part of Indo-Gangetic Plain. Issue 2 (7th February 2019) - Bagchi, Saikat; Raghukanth, S. T. G.
ABSTRACT: In spite of high seismic risk, there is no numerical model of Indo-Gangetic Plain. In this paper, seismic response of the central part of Indo-Gangetic Plain, i.e., Ganga Plain is studied using a two-dimensional plane strain finite element model. Seismic source is assumed to be located beneath the Himalayas near Himalayan Frontal Thrust. Basin response is simulated for a hypothetical Mw 8.0 Himalayan earthquake. Ground motion amplification and sensitive frequency band of the basin, obtained from the numerical simulation, show that the sediment depth and epicentral distance at a site play significant role in the seismic response of the site.